1996
DOI: 10.1017/s0022215100134000
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumour arising in the nasal cavity: report of a case

Abstract: The nasal and the paranasal sinuses are a rare site for solitary fibrous tumours. There have been no previously reported cases in the English literature, with eight cases in the world literature (Witkin and Rosai, 1991; Zuckerberg et al., 1991). We present a case of a solitary fibrous tumour arising in the nasal cavity and review the previous reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…Recently, SFTs have been reported in the head and neck area, parapharyngeal space (3), tongue (4), larynx (3,5) and parotid gland (6). SFTs of the nasal cavity and paranasal sinuses are extremely rare: to date only 21 cases of SFTs arising from these locations have been reported (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SFTs have been reported in the head and neck area, parapharyngeal space (3), tongue (4), larynx (3,5) and parotid gland (6). SFTs of the nasal cavity and paranasal sinuses are extremely rare: to date only 21 cases of SFTs arising from these locations have been reported (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…SFTs of the sinonasal cavity are rare, with fewer than 30 cases reported in the English literature to date. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Although several case reports and clinical studies have mentioned imaging findings of SFTs in this region, 6,12,15 the specific imaging characteristics of sinonasal SFT have not been detailed in the literature. We present the CT and MR imaging features of 5 patients with sinonasal SFTs proved by histopathology.…”
mentioning
confidence: 99%
“…[1][2][3][4] The first case in the English literature of a solitary fibrous tumor arising in nasal cavity was reported by String fellow in 1996 in a 59 year old woman. 13 In a review of literature, Alobid et al 14 have mentioned 21 cases of primary SFT arising in nasal cavity and paranasal sinuses. Ahire et al 10 have reported a case of SFT involving maxillary sinus and have mentioned that previously only 24 cases of SFT of nose and paranasal sinuses are reported in English literature.…”
Section: Disscusionmentioning
confidence: 99%